The hoard of the Early Iron Age at the settlement of Dianovo-II (Belozersk district of the Kurgan region) - Riabinina E.A.; Maslyuzhenko D.N.; Spiridonov I.А.; Usachev E.V. (Вестник археологии, антропологии и этнографии, 2023)
In 2016, in the area of Dianovo village of the Belozersk district of the Kurgan region (West Siberia), a hoard of the Early Iron Age artifacts was found. While examining the area for the identification of structures of the Civil War period, a round-bottomed vessel was accidentally discovered. Inside the container, there was a massive rectangular bronze plate, glass beads, and fragments of jewelry, including bronze strings, bronze plaques in the shape of fish and four-petal plaques strung on leather cords, all wrapped in organic material (felt?). In total, the Dianovo treasure contains 370 objects made of bronze and glass, assembled within a single set, classified as women’s. At present, this is one of very few elements of the women’s costume of the Early Iron Age that have been best preserved in the Southern Trans-Urals. These finds were transferred to the archaeological laboratory of the Kurgan State University, and later the archaeological survey was carried out at the discovery location by I.A. Spiridonov. The purpose of this research is a typological description of the contents of the hoard, its chronological analysis, and a possible reconstruction of the bronze ornament. The main research materials are the container in which the treasure was found — a ceramic round-bottomed vessel, a set of bronze objects that piece together a female (breast?) adornment, a set of glass beads of three types (rounded blue, black (square and rounded) with festoon-like white and yellow pattern), and a massive bronze plate with traces of manufacturing, which probably had the purpose of an ingot. Based on the analysis of the materials, it has been established that the hoard was most likely left by the population of the Gorokhovskaya Culture. This conclusion was made on the basis of the shape and features of the ceramic vessel. This is also supported by the location of the treasure and the general dating of individual items: glass beads of the Black Sea origin have numerous similarities in the sites and are quite clearly dated by these analogues to the 4th–3rd c. BC. The dating of other items of the hoard — elements of the bronze ornament and a bronze ingot-plate is complicated due to the lack of clearly dated analogues or chronological duration of their use. Judging by the composition and carefulness of packing of the items, this hoard apparently was of a situational (possibly in the event of an attack) and returnable character.